2001
DOI: 10.1039/b105640a
|View full text |Cite
|
Sign up to set email alerts
|

3′-Amino-2′,4′-BNA: novel bridged nucleic acids having an N3′→P5′ phosphoramidate linkage

Abstract: Novel oligonucleotide analogues, containing a 3'-amino-2',4'-BNA unit, were successfully synthesized, and they showed superior duplex and triplex forming ability as well as BNA itself, along with remarkable enzymatic stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 23 publications
0
25
0
Order By: Relevance
“…In 1998 Singh et al [5] reported that an LNA oligonucleotide (5r-T13t-3 ~, LNA in capital letters, DNA in lower case) remained intact for more than 60 min upon incubation with snake venom phosphodiesterase (SVPD), while the control DNA oligonucleotide was completely degraded after 10 min. This finding was later confirmed by several investigators [6,7], but, quite puzzling, was not observed by Obika et al [8], who reported that the resistance to digestion by SVPD of a poly(dt)10 oligonucleotide containing an LNA at the penultimate 3~-position could be dramatically increased if the LNA was substituted by a 3~-amino-LNA (LNA combined with the N3t-P5~phosphoramidate linkage).…”
Section: Stability Of Lna To Nucleasesmentioning
confidence: 69%
“…In 1998 Singh et al [5] reported that an LNA oligonucleotide (5r-T13t-3 ~, LNA in capital letters, DNA in lower case) remained intact for more than 60 min upon incubation with snake venom phosphodiesterase (SVPD), while the control DNA oligonucleotide was completely degraded after 10 min. This finding was later confirmed by several investigators [6,7], but, quite puzzling, was not observed by Obika et al [8], who reported that the resistance to digestion by SVPD of a poly(dt)10 oligonucleotide containing an LNA at the penultimate 3~-position could be dramatically increased if the LNA was substituted by a 3~-amino-LNA (LNA combined with the N3t-P5~phosphoramidate linkage).…”
Section: Stability Of Lna To Nucleasesmentioning
confidence: 69%
“…For example, each of the 2′,4′-BNA modification (16-21) and the N3′fP5′ phosphoramidate modification (27)(28)(29)(30)(31)(32)(33) increased T m for both duplex and triplex significantly. However, thermal stability for both duplex and triplex produced by the combination of these two modifications was lower than that by the 2′,4′-BNA modification alone (34). Strand interference and no cooperativity of the two stabilizing methods occurred.…”
Section: Discussionmentioning
confidence: 97%
“…However, combinations of two stabilization methods have occasionally resulted in unexpectedly small effects. For example, while each of 2′-O,4′-C-methylene-bridged nucleic acid (2′,4′-BNA/LNA) modification (15-26) and N3′fP5′ phosphoramidate modification (27-33) of nucleic acid strands increases the thermal dissociation temperatures of duplex and triplex significantly, the combination of these two modifications results in less stabilizing activity than the 2′,4′-BNA modification alone (34,35). In another example, while †…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…5). [15][16][17][18][19][20][21][22][23][24] Each BNA has its own sugar conformation and shows unique and interesting properties when it is incorporated into oligonucleotides. Among these BNAs, 2Ј,4Ј-BNA was independently synthesized by the group of Wengel et al immediately after our first report, [25][26][27][28][29] and it is called a locked nucleic acid (LNA) and is now commercially available.…”
Section: Introductionmentioning
confidence: 99%